2024
DOI: 10.1002/anie.202316428
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Directed Evolution in Mammalian Cells Yields a Hyperefficient Pyrrolysyl tRNA for Noncanonical Amino Acid Mutagenesis

Delilah Jewel,
Rachel E. Kelemen,
Rachel L. Huang
et al.

Abstract: Heterologous tRNAs used for noncanonical amino acid (ncAA) mutagenesis in mammalian cells typically show poor activity. We recently introduced a virus‐assisted directed evolution strategy (VADER) that can enrich improved tRNA mutants from naïve libraries in mammalian cells. However, VADER was limited to processing only a few thousand mutants; the inability to screen a larger sequence space precluded the identification of highly active variants with distal synergistic mutations. Here, we report VADER2.0, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Recently, researchers have employed a virus-mediated gene delivery technique to conduct directed evolution of tRNA within animal cells called virus-assisted directed evolution strategy (VADER) ( Jewel et al, 2023 ; Jewel et al, 2024 ). They employed a selection system diverging from the commonly used positive/negative selection method.…”
Section: Trna Engineering Strategiesmentioning
confidence: 99%
“…Recently, researchers have employed a virus-mediated gene delivery technique to conduct directed evolution of tRNA within animal cells called virus-assisted directed evolution strategy (VADER) ( Jewel et al, 2023 ; Jewel et al, 2024 ). They employed a selection system diverging from the commonly used positive/negative selection method.…”
Section: Trna Engineering Strategiesmentioning
confidence: 99%
“…While bacterial platforms remain the primary avenue for tRNA engineering, recent work established the virus-assisted directed evolution of tRNA (VADER) (Jewel et al, 2023;Jewel et al, 2024). VADER facilitates the screening of >60,000 unique tRNA variants in human cultured cells, offering a novel avenue for rapid human sup-tRNA discovery.…”
Section: Translation Deficiencies Of Sup-trna Therapeutic Candidatesmentioning
confidence: 99%
“…This emphasizes that the protein synthesis machinery differs between hosts, and tRNA sequences improved in one host cannot necessarily be transferred to others. Follow-up research identified a tRNA Pyl variant, PyOtR, with markedly improved activity over A2.1 in mammalian cells ( Jewel et al, 2024 ). PyOtR contained a similarly GC-rich acceptor stem, with a bias for 5′ G residues, but also demonstrated an essential G5:U68 wobble pair—usually detrimental in tRNA acceptor stems ( Santoro et al, 2003 ).…”
Section: Trna Engineering In Eukaryotic Systemsmentioning
confidence: 99%